Concepts of Thai Contemporary Dance “Phra Lor” by Naraphong Charassri - Chimphut, Rungnapha (Mekong-Salween Civilization Studies Journal, 2016)
The present research examines the concepts and form of the Thai contemporary dance ‘Phra Lor’ by Naraphong Charassri, performed at Maepra Fatima School to promote the collaboration of teachers, students, and parents in carrying out Thai art and cultural activities. The findings revealed that the dance contributed to the preservation of the theme and value of the literary work ‘Lilit Phra Lor’ by incorporating symbolic concepts and visual and dance arts theories into a performance suitable for teenagers presented through several important components. First, the storyline adapted the theme of love in ‘Lilit Phra Lor’ but reduced its violence elements to accommodate teenage viewers. Second, the erformance featured natural and simple yet clear delivery of meanings. Third, the ostume took into consideration the storyline and roles of characters. Fourth, the music and sound matched the Lanna culture presented in the story, such as the application of tremolos in lullaby singing. Inaddition, the narration was conducted in a smooth tone to highlight the beauty of the story. Fifth, the stage set was formed with the performers standing as the background, and the props were made from materials characterizing the Lanna culture. Sixth, the performance space applied composition theories and considered the roles of characters, resulting in a multi-faceted yet coherent show. Seventh, the lighting relied on natural light to create an appropriate mood and atmosphere. Finally, the performers were recruited from skilled individuals of the right personality traits and age able to preserve the theme and value of ‘Lilit Phra Lor’ effectively.